2016
DOI: 10.1002/star.201600209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single or combined administration of resistant starch and chitosan oligosaccharides on insulin resistance in rats fed with a high‐fat diet

Abstract: Abbreviations: COS, chitosan oligosaccharide; FTIR, Fourier transform infrared spectroscopy; HOMA-IR, homeostasis model of assessment for insulin resistance index; IR, insulin resistance; QUICKI, quantitative insulin sensitivity check index; RS, resistant starch; SEM, scanning electron microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Decreases in insulin secretion and sensitivity can result in reduced hepatic glycogen synthesis, which accelerates metabolic disorders and the development of diabetes. [ 34 ] As shown in Figure , the liver glycogen content of the model group was reduced to 6.1 mg · g −1 liver weight, a significant difference compared with the NC group. Dietary intervention with CY and RS over 12 weeks significantly increased liver glycogen content, reaching 13.32 and 12.43 mg · g −1 , respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Decreases in insulin secretion and sensitivity can result in reduced hepatic glycogen synthesis, which accelerates metabolic disorders and the development of diabetes. [ 34 ] As shown in Figure , the liver glycogen content of the model group was reduced to 6.1 mg · g −1 liver weight, a significant difference compared with the NC group. Dietary intervention with CY and RS over 12 weeks significantly increased liver glycogen content, reaching 13.32 and 12.43 mg · g −1 , respectively.…”
Section: Resultsmentioning
confidence: 94%
“…In vivo COS administration did not demonstrate any antidiabetic/hypocholesterolemic effects, since glycemia and cholesterol levels in GK rats were not altered [100]. In a recent study [101], the consumption of COS with complexes to resistant starch produced a higher capability for insulin sensitivity revival. Gene expression of liver tissues obtained from COS-injected rats approved that this effect may be due to increase in the liver glucose alteration through activation of GS2 as well as GYG1, decrease in gluconeogenesis through activation of G6PC1, and change in glucolipid metabolism through activation of Insig-2.…”
Section: Resultsmentioning
confidence: 99%
“…A new absorption peak at 1560.88 cm −1 appeared in the COS-RS complex spectra, and the shape of typical absorption peaks for starch from 1180 to 953 cm −1 also changed. The results suggested that the consumption of COS-RS complexes exerted a more efficient recovery of insulin sensitivity compared to individual treatments [77]. Herbal supplements are currently available as a safer alternative to manage obesity.…”
Section: Application Of Ir Spectroscopy and Microscopy In Obesity Resmentioning
confidence: 95%